Are NFL Arrestees Violent Specialists or High Frequency Offenders or Both?. Issue 4 (2nd April 2016) - Leal, Wanda; Gertz, Marc; Piquero, Alex R.
ABSTRACT: Although recent research showed that NFL players have a higher violent crime arrest rate, it remains unclear whether, at the individual-level, NFL players who are arrested are specializing in violent crimes or whether their involvement in violence is driven largely by their high frequency of offending. Using two publically available databases on NFL player arrests, our results show that high frequency offending is rare among the arrested NFL players, that non-white players are more chronic than white players, and that the likelihood of violence is largely driven by high frequency offending—especially among non-white players. Importantly, there appears to be no specialization-in-violence among this sample of arrested NFL players.